From Microcosm to Macrocosm : Individual households and cities in Ancient Egypt and Nubia - Budka, Julia (SIdestone Press, 2018)
Intro -- Introduction -- Julia Budka* and Johannes Auenmüller** -- Individual Households and Cities in Ancient Egypt and Nubia -- A short summary of the state-of-the-art -- Julia Budka* -- The Development of Two Early Urban Centres in Upper Egypt During the 3rd Millennium BC -- The examples of Edfu and Dendara -- Nadine Moeller* and Gregory Marouard** -- Ancient Gold Mining Settlements in the Eastern Deserts of Egypt and Nubia -- Dietrich Klemm* and Rosemarie Klemm** -- Kerma and Dokki Gel -- Evidence of impressive changes in the urban architecture at the beginning of the New Kingdom in Nubia -- Charles Bonnet* -- The Many Ethnicities in Avaris -- Evidence from the northern borderland of Egypt -- Manfred Bietak* -- Egyptians and Nubians in the Early New Kingdom and the Kushite Background -- Bruce Williams* -- AcrossBorders -- Five seasons of work in the Pharaonic town, Sai Island -- Julia Budka* -- Image Based Modelling and Kite Aerial Photography on Sai Island -- Martin Fera* and Cajetan Geiger** -- The Fortifications of the Pharaonic Town on Sai Island -- A reinvestigation -- Ingrid Adenstedt* -- Pots & People -- Ceramics from Sai Island and Elephantine -- Julia Budka* -- From Macro Wares to Micro Fabrics and INAA Compositional Groups -- The pottery corpus of the New Kingdom town on Sai Island (Northern Sudan) -- Giulia D'Ercole* and Johannes H. Sterba** -- Tomb 26 in Cemetery SAC5 on Sai Island -- Julia Budka* -- Life History of Khnummose and Selected Anthropological Finds from Tomb 26, Sai Island, Sudan -- Marlies Wohlschlager* and Andrea Stadlmayr** -- The Fortified Settlement at Tombos and Egyptian Colonial Strategy in New Kingdom Nubia -- Stuart Tyson Smith* and Michele R. Buzon** -- Urbanism in Nubia and the New Kingdom Temple Towns -- Jördis Vieth* -- New Kingdom Towns in Upper Nubia.